Transcriptome‐based screening of ion channels and transporters in a migratory chondroprogenitor cell line isolated from late‐stage osteoarthritic cartilage. Issue 11 (18th May 2021) - Matta, Csaba; Lewis, Rebecca; Fellows, Christopher; Diszhazi, Gyula; Almassy, Janos; Miosge, Nicolai; Dixon, James; Uribe, Marcos C.; May, Sean; Poliska, Szilard; Barrett‐Jolley, Richard; Fodor, Janos; et al.
Abstract: Chondrogenic progenitor cells (CPCs) may be used as an alternative source of cells with potentially superior chondrogenic potential compared to mesenchymal stem cells (MSCs), and could be exploited for future regenerative therapies targeting articular cartilage in degenerative diseases such as osteoarthritis (OA). In this study, we hypothesised that CPCs derived from OA cartilage may be characterised by a distinct channelome. First, a global transcriptomic analysis using Affymetrix microarrays was performed. We studied the profiles of those ion channels and transporter families that may be relevant to chondroprogenitor cell physiology. Following validation of the microarray data with quantitative reverse transcription‐polymerase chain reaction, we examined the role of calcium‐dependent potassium channels in CPCs and observed functional large‐conductance calcium‐activated potassium (BK) channels involved in the maintenance of the chondroprogenitor phenotype. In line with our very recent results, we found that the KCNMA1 gene was upregulated in CPCs and observed currents that could be attributed to the BK channel. The BK channel inhibitor paxilline significantly inhibited proliferation, increased the expression of the osteogenic transcription factor RUNX2, enhanced the migration parameters, and completely abolished spontaneous Ca 2+ events in CPCs. Through characterisation of their channelome we demonstrate that CPCs are a distinct cell population but are highly similar to MSCs in many respects. This study adds key mechanistic data to the in‐depth characterisation of CPCs and their phenotype in the context of cartilage regeneration. Abstract : Chondrogenic progenitor cells (CPCs) may be used as an alternative source of cells with potentially superior chondrogenic potential compared to mesenchymal stem cells (MSCs) and could be exploited for future regenerative therapies targeting articular cartilage in degenerative diseases such as osteoarthritis (OA). In this study, we analysed the channelome of CPCs and MSCs using Affymetrix microarrays and quantitative reverse transcription‐polymerase chain reaction. We examined the role of calcium‐dependent potassium channels in CPCs and observed functional large‐conductance calcium‐activated potassium (BK) channels involved in the maintenance of the chondroprogenitor phenotype. We demonstrate that CPCs are a distinct cell population but are highly similar to MSCs in many respects.